2017
DOI: 10.1109/jsyst.2015.2441720
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Vehicles for E-Health Applications: A Potential Game for Optimal Network Capacity

Abstract: Wireless technologies are pervasive to support ubiquitous healthcare applications. However, a critical issue of using wireless communications under a healthcare scenario rests at the electromagnetic interference (EMI) caused by RF transmission, and a high level of EMI may lead to a critical malfunction of medical sensors. In view of EMI on medical sensors, we propose a power control algorithm under a noncooperative game theoretic framework to schedule data transmission. Our objective is to ensure that the nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It is expected that the advent of 5G technologies will play an active part in providing patient-oriented healthcare applications which can be easily managed by the patient or the carer. It is expected that 5G networks would carry a significantly higher volume of data while maintaining reliability [70], [71]. The critical requirement for 5G networks is ultra-low latency which will allow the deployment of mission critical applications such as tele-consulting, tele-surgery etc.…”
Section: Healthcarementioning
confidence: 99%
“…It is expected that the advent of 5G technologies will play an active part in providing patient-oriented healthcare applications which can be easily managed by the patient or the carer. It is expected that 5G networks would carry a significantly higher volume of data while maintaining reliability [70], [71]. The critical requirement for 5G networks is ultra-low latency which will allow the deployment of mission critical applications such as tele-consulting, tele-surgery etc.…”
Section: Healthcarementioning
confidence: 99%
“…The coming 5G provides a wider perspective in terms of those parameters. The surveys in [ 18 , 19 ] concluded that 5G, being reliable, can handle voluminous data having three properties—embb, urllc, and umtc—that allow tele-consulting and telesurgery applications to work. Working of WTS is just like Mater–Slave system where a Human surface interface (HSI) having a video console, headphones, and haptic device at the master side can operate on the patient using a robot by giving certain commands.…”
Section: Generations and Challenges Of Healthcare Systemsmentioning
confidence: 99%
“…Similarly, each organization, such as intelligent transportation, e-health, and military usage, has different perspectives on IoVs. 54 …”
Section: Incorporation Of Iovsmentioning
confidence: 99%